2018
DOI: 10.1038/s41598-018-29334-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxford Nanopore’s MinION Sequencing Device for Microbial Whole Genome Sequencing Applications

Abstract: The MinION sequencer (Oxford Nanopore Technologies) is a paradigm shifting device allowing rapid, real time long read sequencing of nucleic acids. Yet external benchmarking of this technologies’ capabilities has not been extensively reported, nor has thorough evaluation of its utility for field-based analysis with sub-optimal sample types been described. The aim of this study was to evaluate the capability of the MinION sequencer for bacterial genomic and metagenomic applications, with specific emphasis placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(183 citation statements)
references
References 31 publications
6
168
2
Order By: Relevance
“…In a published research study 126 , mNGS-based detection of Ebola and chikungunya virus infections on a nanopore sequencer was possible in <10 minutes of sequencing time and in <6 hours of sample-to-answer turnaround time overall. Research studies have also demonstrated the clinical potential of nanopore sequencing in targeted universal 16S ribosomal RNA (rRNA) bacterial detection 127 , microbiome analyses 128 , whole-genome sequencing of bacteria 129 and outbreak viruses 44,45,47 , RNA sequencing (RNA-seq) using standardized controls 130 and diagnosis of prosthetic joint 131 and lower respiratory infections 99 . Untargeted approaches such as mNGS or whole-transcriptome RNA-seq, however, may be limited by the lower throughput of nanopore sequencing relative to short-read sequencing such as with an Illumina instrument.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In a published research study 126 , mNGS-based detection of Ebola and chikungunya virus infections on a nanopore sequencer was possible in <10 minutes of sequencing time and in <6 hours of sample-to-answer turnaround time overall. Research studies have also demonstrated the clinical potential of nanopore sequencing in targeted universal 16S ribosomal RNA (rRNA) bacterial detection 127 , microbiome analyses 128 , whole-genome sequencing of bacteria 129 and outbreak viruses 44,45,47 , RNA sequencing (RNA-seq) using standardized controls 130 and diagnosis of prosthetic joint 131 and lower respiratory infections 99 . Untargeted approaches such as mNGS or whole-transcriptome RNA-seq, however, may be limited by the lower throughput of nanopore sequencing relative to short-read sequencing such as with an Illumina instrument.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Fourth, the variable level of enrichment and coverage at a given nucleotide position achieved using MSSPE might preclude it from high-fidelity viral quasispecies analysis or whole-genome assembly at high coverage depth, especially on the nanopore sequencer given current sequencing error rates of ~5-10% (ref. 46 ). For these applications, MSSPE may be synergistic with complementary tiled multiplex PCR or capture probe enrichment approaches, as demonstrated here and previously 29 .…”
Section: Discussionmentioning
confidence: 99%
“…While the MinIon sequencer currently has a higher error rate than Illumina sequencers, a recent evaluation of 15 MinIon sequencing runs reported the average error rate to be 6% when using the same r9.4 flowcells as our study (Tyler et al, 2018). With a MinIon error rate of 6%, any species-level detections with blast % identities <95% should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 69%